Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s00284-015-0885-8
|View full text |Cite
|
Sign up to set email alerts
|

The Accordant Trend of Both Parameters (rgs Expression and cAMP Content) Follows the Pattern of Development of Fruiting Body in Volvariella volvacea

Abstract: The formation of fruiting body in Volvariella volvacea is affected by endogenous genes and environmental factors. However, its regulation at a molecular level is still poorly understood. To study the genes involved in the formation of fruiting body, we cloned a new regulator of the G protein signaling (RGS) encoding gene (rgs) from V. volvacea. Phylogenetic analysis showed that RGS in V. volvacea and other basidiomycete RGS proteins from Schizophyllum commune and Coprinus cinereus belong to the same clade. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…V. volvacea is the fastest growing species of edible fungi, requiring only 7 to 12 days from sowing to fruiting and 30 days to cultivation. In addition, it has a high economic efficiency owing to only requiring a simple planting method and ample availability of raw materials [ 17 , 19 ]. Filamentous fungi are important organisms frequently studied by RT-qPCR; however, identification of suitable reference genes for RT-qPCR of fungal species has received little attention.…”
Section: Introductionmentioning
confidence: 99%
“…V. volvacea is the fastest growing species of edible fungi, requiring only 7 to 12 days from sowing to fruiting and 30 days to cultivation. In addition, it has a high economic efficiency owing to only requiring a simple planting method and ample availability of raw materials [ 17 , 19 ]. Filamentous fungi are important organisms frequently studied by RT-qPCR; however, identification of suitable reference genes for RT-qPCR of fungal species has received little attention.…”
Section: Introductionmentioning
confidence: 99%
“…cAMP is a second messenger in both eukaryotes and prokaryotes and plays a key role in fungal development. Lu et al [ 29 ] found that cAMP was highly expressed in the primordium tissue while digging for genes regulating the development of V. volvacea and speculated that cAMP was involved in the primordium formation of V. volvacea . At the same time, some studies have demonstrated that the cAMP content of Aspergillus nidulans and Dictyostelium reaches a peak when spores germinate and mature [ 30 , 31 , 32 ]—that is to say, the cAMP pathway has also been implicated in the development of other fungi.…”
Section: Discussionmentioning
confidence: 99%
“…First, Fvcpc2 might be required for the normal production of cellular cAMP. The cAMP level mediates vegetative growth and fruiting body formation in C. cinerea, S. commune, and V. volvacea (Kinoshita et al, 2002;Kües et al, 2004;Lu et al, 2015). The second messenger cAMP, produced by adenylate cyclase, is involved in many developmental processes in fungi (Lengeler et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The CPC-2 ortholog Gib2 in C. neoformans functions as a typical Gβ subunit, which regulates the cellular cAMP (cyclic AMP) level (Palmer et al, 2006). The cAMP level mediates vegetative growth and fruiting body formation in C. cinerea, S. commune and V. volvacea (Kinoshita et al, 2002;Kües et al, 2004;Lu et al, 2015). In order to detect whether Fvcpc2 is related to cAMP production, transcript levels of gene10451 and gene8023, which respectively encode adenylate cyclase and protein kinase A catalytic subunit-2, were comparatively analyzed in all Fvcpc2 knockdown strains and the wild-type strain after fruiting induction in F. velutipes.…”
Section: Fvcpc2 Regulates Genes Involved In Camp Signaling Pathway Inmentioning
confidence: 99%